WEB ACCESSIBLE MULTIACCOUNT CONFIGURABLE CLIENT EMAIL APPLICATIO - Ratecki, Krzysztof; Sakowicz, Bartosz; Wojtowski, Marcin; Napieralski, Andrzej (International Journal of Computing, 2014)
The article presents alternative ways of checking emails and how to make an application mail enabled using library of J2EE Platform – JavaMail API. The article describes application attainable from WEB browser based on JSP Scripts and Java servlets. Application allows for access to multiple email accounts through one web page.